A Tale of Two Authors: Valenzuela and Borges - Sharon Magnarelli (Studies in 20th & 21st Century Literature, 2002)
Although Luisa Valenzuela and Borges were friends for many years, it is only recently that we find traces of that friendship in her narrative. "La calesita" and "El otro libro," published in 1998 and 1999 respectively, evoke many of the elements we find in Borges's narrative. The latter story, which is the main focus of this study, employs nearly all the narrative elements we have come to associate with the Argentine master. Nonetheless, a single sign is changed as Borges's male characters are replaced by females in Valenzuela's work. The end result is a tribute to Borges but one that challenges us to perceive the world differently and to seek the "god behind God [that] begins the tale/game" of the master narratives and to whom Borges alludes in his poem, "Ajedrez."
Keywords: Luisa Valenzuela; Borges; la calesita; el otro libro; friendship; Argentine literature